2013
DOI: 10.1186/1471-2229-13-55
|View full text |Cite
|
Sign up to set email alerts
|

Energy status of ripening and postharvest senescent fruit of litchi (Litchi chinensis Sonn.)

Abstract: BackgroundRecent studies have demonstrated that cellular energy is a key factor switching on ripening and senescence of fruit. However, the factors that influence fruit energy status remain largely unknown.ResultsHPLC profiling showed that ATP abundance increased significantly in developing preharvest litchi fruit and was strongly correlated with fruit fresh weight. In contrast, ATP levels declined significantly during postharvest fruit senescence and were correlated with the decrease in the proportion of edib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 64 publications
5
54
0
Order By: Relevance
“…Therefore, a higher ATP status can weaken the TCA cycle and result in the lower respiration rate. Taken together, we concluded that the decreased respiration rate in NaHS-treated samples might be attributed to the higher ATP level, which is also in accordance with the findings reported by Wang et al (2013), showing that the respiration rates could be inhibited by high ATP level during storage of litchi.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a higher ATP status can weaken the TCA cycle and result in the lower respiration rate. Taken together, we concluded that the decreased respiration rate in NaHS-treated samples might be attributed to the higher ATP level, which is also in accordance with the findings reported by Wang et al (2013), showing that the respiration rates could be inhibited by high ATP level during storage of litchi.…”
Section: Discussionsupporting
confidence: 91%
“…Postharvest preconditioning treatments at moderate temperatures before cold storage allow a progressive adaptation of the fruit to chilling temperatures. In zucchini, it has been reported that temperature-preconditioning treatments at 15 °C for two days, before storage at the chilling temperature of 4 °C, reduces CI symptoms by preventing the deterioration of the cell membrane and improving the antioxidant status of the preconditioned fruit [ 60 , 122 , 123 ].…”
Section: Postharvest Treatments That Reduce Oxidative Stress and Cmentioning
confidence: 99%
“…It is known that energy metabolism plays significant roles in the postharvest physiology of fruit and vegetables, and that ATP, ADP and AMP levels, as well as energy status, are affected by environmental factors, mainly by low oxygen levels (Saquet et al, 2001;Wang et al, 2013;Huang et al, 2014). A reduction of the cellular energy charge together with the accumulation of fermentative metabolites are generally considered to be common responses to hypoxia in aerobic organisms, including plants, and even a slight decrease in oxygen concentration provokes a drop in the cellular energy status (ATP/ADP ratio) (Geigenberger, 2003).…”
Section: Introductionmentioning
confidence: 99%